Evidence of the Active Participation of Women in the Intergroup Conflict Based on the Use of Aggression and Cooperation - Fajardo-Cuevas, G (Nature Research, 2023)
Intergroup conflict has been a persistent aspect of human societies since the emergence of our species. Various researchers have proposed that competition between groups has acted as a key selective force throughout human evolutionary history. Such intergroup competition for limited resources exacerbated the expression of intergroup aggression and intragroup cooperation. Furthermore, it would have a sexual dimorphism, with men demonstrating increased sensitivity to conflict threats—in order to maximize reproductive opportunities—, while women generally reject from active engagement in intergroup conflict. In the present study, we conducted behavioral experiments under controlled laboratory conditions to measure cooperation and aggression from using virtual games, specifically the Public Good Games and the Point Subtraction Aggression Paradigm, in a sample of 541 participants. We created control and experimental intergroup competition scenarios, where aggression and cooperation were necessary to increase monetary rewards. Our results shows that men modulate aggression and cooperation in the presence of intergroup conflict. In addition, our data also reveals that women cooperate more than men and display heightened levels of cooperation and aggression when confronted with intergroup conflict. These findings prompt a reevaluation of current functional theoretical models concerning the role of women in intergroup conflict and suggest that the dynamics of human aggression and cooperation may be more nuanced than previously believed. © 2023, Springer Nature Limited.